Student perception of online learning activities during COVID-19 pandemic: Psychological constraints and factors - Latifatul Fazriyah; Sri Kusrohmaniah (Institute of Advanced Engineering and Science, 2023)
COVID-19 pandemic has brought many changes to our lives. One of the prominent changes is the offline learning model changed to online. This change may have an impact on the effectiveness of the learning process and students’ understanding of the knowledge conveyed by the lecturer. So, a further analysis needs to be done. In this study, students’ perceptions of online learning during the pandemic were explored. The goal was to find out what students think and feel while participating in online learning during pandemic so that in the future lecturers are able to create or choose the more effective learning models for their classes. This research was conducted using the phenomenological method on several students’ majoring in health science who were undergoing school from home (SFH). Data collection was carried out using the depth interview method by telephone and WhatsApp chat according to the flexibility of the participants’ time. The finding of this research showed that e-learning programs carried out during the pandemic actually put more mental pressure on students’ and decrease their learning motivation, especially in early days of the program. This happened due to the lecturer and university lack of readiness in carrying out the program.